HUKUM MEMPERCAYAI ZODIAK DALAM PERSPEKTIF AL-QUR’AN: TELAAH SURAT AL-AN’AM AYAT 67 - Abdul Hadi (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
This study aims to examine the ruling on believing in zodiac signs from the perspective of the Qur’an through an analysis of Surah Al-An'am verse 76. In modern society, zodiac beliefs are not only used for entertainment but also as references for understanding personality, predicting fate, and making life decisions. This research employs a qualitative method with a thematic (maudhu’i) exegesis approach, supported by analyses of classical and contemporary tafsir literature. The examined verse illustrates the process of truth-seeking by Prophet Ibrahim, who observed a star as a supposed deity but rejected it due to its transient nature. This indicates that celestial bodies do not possess absolute authority over human life. The findings reveal that believing in zodiac signs as determinants of fate contradicts the principle of monotheism (tawhid) and may lead to shirk, as it attributes divine power to other than Allah. Therefore, believing in zodiac signs as determinants of destiny is not justified in Islamic teachings, although their use purely for entertainment without belief does not fall under the same ruling.